Syntrophin-2 is required for eye development in Drosophila. - Nagai, R.; Hashimoto, R.; Tanaka, Y.; Taguchi, O.; Sato, M.; Matsukage, A.; Yamaguchi, M. (Experimental Cell Research, 2010)
Syntrophins are components of the dystrophin glycoprotein complex (DGC), which is encoded by causative genes of muscular dystrophies. The DGC is thought to play roles not only in linking the actin cytoskeleton to the extracellular matrix, providing stability to the cell membrane, but also in signal transduction. Because of their binding to a variety of different molecules, it has been suggested that syntrophins are adaptor proteins recruiting signaling proteins to membranes and the DGC. However, critical roles in vivo remain elusive. Drosophila Syntrophin-2 (Syn2) is an orthologue of human gamma 1/gamma 2-syntrophins. Western immunoblot analysis here showed Syn2 to be expressed throughout development, with especially high levels in the adult head. Morphological aberrations were observed in Syn2 knockdown adult flies, with lack of retinal elongation and malformation of rhabdomeres. Furthermore, Syn2 knockdown flies exhibited excessive apoptosis in third instar larvae and alterations in the actin localization in the pupal retinae. Genetic crosses with a collection of Drosophila deficiency stocks allowed us to identify seven genomic regions, deletions of which caused enhancement of the rough eye phenotype induced by Syn2 knockdown. This information should facilitate identification of Syn2 regulators in Drosophila and clarification of roles of Syn2 in eye development.